Keterbukaan Informasi Mengenai Perlindungan Konsumen Merupakan Informasi yang Memiliki Firm Specific - Sri Hutomo (Bina Nusantara University, 2002)
Article presents information on consumer protection by showing E.M. Jackson cases versus Nestle on product liability and breaking the law. The justice decision, Foreign naturaldoctrine Reasonable Expectation test, and strict liablility.